Impact of the Trump Administration's Expanded Global Gag Rule Policy on Family Planning Service Provision in Ethiopia. Issue 2 (31st May 2022) - Sully, Elizabeth A.; Shiferaw, Solomon; Seme, Assefa; Bell, Suzanne O.; Giorgio, Margaret
Abstract: The Global Gag Rule (GGR) makes non‐U.S. nongovernmental organizations (NGOs) ineligible for U.S. Government global health funding if they provide, refer, or promote access to abortion. This study quantitatively examines the impacts of the GGR on family planning service provision in Ethiopia. Using a panel of health facilities (2017–2020), we conduct a pre–post analysis to investigate the overall changes in family planning service provision before and after the policy came into effect in Ethiopia. Our pre–post analyses revealed post‐GGR reductions in the proportions of facilities reporting family planning provision through community health volunteers (−5.6, 95% CI [−10.2, −1.0]), mobile outreach visits (−13.1, 95% CI [−17.8, −8.4]), and family planning and postabortion care service integration (−4.8, 95% CI: [−9.1, −0.5]), as well as a 6.1 percentage points increase in contraceptive stock‐outs over the past three months (95% CI [−0.6, 12.8]). We further investigate the impacts of the GGR on facilities exposed to noncompliant organizations that did not sign the policy and lost U.S. funding. We do not find any significant additional impacts on facilities in regions more exposed to noncompliant organizations. Overall, while the GGR was slow to fully impact NGOs in Ethiopia, it ultimately resulted in negative impacts on family planning service provision.